2015
DOI: 10.1002/14651858.cd007082.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late removal of the laryngeal mask airway (LMA) for general anaesthesia

Abstract: This systematic review suggests that current best evidence comparing early versus late removal of the LMA in participants undergoing general anaesthesia does not demonstrate superiority of either intervention. However, the quality of evidence available is either low or very low. There is a paucity of well designed RCTs and a need for large scale RCTs to demonstrate whether early removal or late removal of the LMA is better after general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…It remains controversial whether the use of the LMA is associated with a higher incidence of laryngospasms. Moreover, removal of the LMA early or after the return of airway reflexes is still debatable [ 45 ]. Our data have shown that there were no statistically significant differences between the FLMA and ETT groups in laryngospasms following the removal of the airway in either the adult or pediatric subgroups during adenotonsillectomy, which is the most common type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It remains controversial whether the use of the LMA is associated with a higher incidence of laryngospasms. Moreover, removal of the LMA early or after the return of airway reflexes is still debatable [ 45 ]. Our data have shown that there were no statistically significant differences between the FLMA and ETT groups in laryngospasms following the removal of the airway in either the adult or pediatric subgroups during adenotonsillectomy, which is the most common type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review by Mathew and colleagues in 2015 concludes that the quality of evidence available is either low or very low and that there is a "paucity of well-designed RCTs (randomised controlled trials) and a need for large scale RCTs to demonstrate whether early removal or late removal of the LMA is better after general anaesthesia". 7 Traditionally, age or even more commonly the personal preference of the anaesthetist guides practice.…”
mentioning
confidence: 99%
“…During sevoflurane anesthesia, the LMA can be safely removed at an approximate minimum alveolar concentration of 0.86 in 95% of anesthetized children; 19 the EC 95 in anesthetized adults is an end-tidal sevoflurane concentration of 1.18%, 20 and that of end-tidal desflurane to allow smooth LMA removal is 3.9% in adults. 21 However, according to a recent systematic review, the current best evidence is inconclusive regarding whether the LMA should be removed early or late in patients undergoing GA. 8 They concluded that there was a smaller risk of coughing after early removal (13.9%) than after late removal (19.4%), and the risk of airway obstruction was higher with early removal (15.6%) than with late removal (4.6%). In addition, there was no difference in the risk of desaturation between early removal (7.9%) and late removal (10.1%), and laryngospasm occurred at similar rates (early removal: 3.3%, late removal: 2.7%).…”
Section: Discussionmentioning
confidence: 99%
“…3–7 In this way, it is currently unclear whether the LMA should be removed at the end of the surgical procedure while the patient remains anesthetized (deep removal) or after the patient is fully awake (awake removal). 8 The quality of evidence available in this regard is considered “low” or “very low;” therefore, well-designed, randomized controlled trials are warranted to demonstrate whether early removal of the LMA after general anesthesia (GA) is better than late removal.…”
Section: Introductionmentioning
confidence: 99%